2008
DOI: 10.2175/193864708x267441
|View full text |Cite
|
Sign up to set email alerts
|

Properties Influencing Fat, Oil, and Grease Deposit Formation

Abstract: Fat, oil, and grease (FOG) deposits are the reported cause of 50 to 75% of sanitary sewer overflows in the United States, resulting in 1.8 3 10 6 m 3 (500 mil. gal) of raw wastewater released into the environment annually. The objective of this research was to characterize the chemical and physical properties of FOG deposits. Twenty-three cities from around the United States contributed FOG samples for the study. The FOG deposits showed a wide range in yield strength (4 to 34 kPa), porosity (10 to 24%), and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 2 publications
6
78
3
Order By: Relevance
“…These high levels of saturated fatty acids in FOG deposits indicate that selective deposition of both saturated acid salts and saturated fatty acids occurred during deposition of FOG deposits since typical cooking oils and animal fats contain significantly lower levels of saturated fatty acids. Palmitic acid is the predominant saturated fatty acid in both cooking oils and animal fats 10 . However, it can be seen that the concentrations of palmitic acid and its salts were 4-5 times higher than concentrations of stearic acid and its salts in these FOG deposits.…”
Section: Fatty Acid Methylmentioning
confidence: 99%
See 1 more Smart Citation
“…These high levels of saturated fatty acids in FOG deposits indicate that selective deposition of both saturated acid salts and saturated fatty acids occurred during deposition of FOG deposits since typical cooking oils and animal fats contain significantly lower levels of saturated fatty acids. Palmitic acid is the predominant saturated fatty acid in both cooking oils and animal fats 10 . However, it can be seen that the concentrations of palmitic acid and its salts were 4-5 times higher than concentrations of stearic acid and its salts in these FOG deposits.…”
Section: Fatty Acid Methylmentioning
confidence: 99%
“…We postulate that after FOG growth has been initiated by the selective preferential precipitation of stearic acid salts, continued deposition will be less selective and other available varieties of fatty acid salts and fatty acids can precipitate on these seed crystals based on their relative availabilities. Interestingly, it has been demonstrated that oleic acid, the major unsaturated fatty acid in both cooking oils and animal fats 10 , undergoes biologically induced cleavage/reduction in estuary sediments to form palmitic acid and stearic acid that are in equilibrium with each other 12 . If these phenomena occur in sewer systems, the stearic acid undergoing equilibration could be captured by available calcium ions to provide an additional source for preferential calcium stearate precipitation.…”
Section: Fatty Acid Methylmentioning
confidence: 99%
“…Sodium oleate decreases the interfacial tension between the frying oil and the thin layer of water on the surface of the fried food, causing migration of the polar lipids from the frying oil to the fried food. Moreover, sodium soaps stimulate the foaming of frying oil and thus accelerate its oxidation 24 . The oxidation reaction, which is promoted by heat, light, and heavy metals, is a radical chain reaction that occurs rapidly under the frying conditions.…”
Section: Chemical and Biological Reactions Related To Fogmentioning
confidence: 99%
“…However, based on the evaluations of vitrified clay pipes VCP , which are used in some countries such as Malaysia, it was found that FOG deposition is not due primarily to the presence of calcium, but can be related to other minerals such as sodium and potassium. Moreover, the presence of high amounts of calcium and sodium in FOG deposits indicates that the deposit not only consist of FOG but also of metallic soaps formed during the hydrolysis reaction 5,23,24 . The aforementioned studies focused on the effect of calcium CaCO 3 on the formation of FOG deposits in sewer pipelines.…”
Section: R Cooh Naoh R Coona H 2 Omentioning
confidence: 99%
“…FOGs in sewer systems mostly originate from kitchens (food production) and showers (the use of soap) (Keener et al 2008). FOGs are very slowly digested and degraded by microorganisms (Cammarota & Freire 2006;Wakelin & Forster 1997).…”
Section: Blockagesmentioning
confidence: 99%